Охоронні розкопки на багатошаровому поселенні Харків, пров. Климовського - Пеляшенко, К.Ю.; Буйнов, Ю.В. (Археологічні дослідження в Україні, 2010)
A brief description of the protective research at the multilayer settlement Kharkiv at Klymovskyi Lane is given. The area studied is represented by the materials of the Bronze Age (Berezhnivsko-Maivska Zrubna and Bondarykhynska cultures), by a child’s grave of the Scythian times and by several finds of Chernyakhivska culture.